Degeneration of Society as an Apocalyptic Symptom: Gender-Driven Crime and Violence in Roberto Bolaño’s 2666 - Jorisse Campado Gumanay (Universitas Sanata Dharma, 2023)
Roberto Bolaño’s five-part novel 2666 is an exploration of the degeneration of the world as seen in the events happening in Santa Teresa, where poor and marginalized women are murdered with no justice in sight. This study focuses on the fourth part of the novel, “The Part About the Crimes”, where the manifold murders and the women victims’ lives unfold while those in power ignore the crisis in town. This paper uses textual analyses and employs Foucault’s approach to power, the feminist views to the Foucauldian approach, and the feminist approach to femicide to elucidate the notions of power explored in the novel, especially in relation to gender power imbalance and destabilization. Through the analysis it was found that the changing power dynamics in a largely patriarchal society and the subversion of accepted gender norms contributed to the rise of femicides in Santa Teresa. The highly unequal society portrayed by Bolaño in his novel serves to reflect modern Latin American society and its perceived chaos, where violence against women have become the norm. The novel’s lack of resolution implies that the world is still very much in that chaos, degeneration continuing to happen, serving as an apocalyptic symptom that signals that the end is coming ever nearer to humanity, an end that is man’s own doing.